PENGARUH ELECTRONIC WORD OF MOUTH DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN DI SHOPEE MARKETPLACE DI BATAM - Saputra, Arnoldus; Saputra, Asron (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2024)
Technological developments bring many changes, especially to the business world This progress is being taken advantage of by entrepreneurs who market their products online. One of them is marketing through the Shopee marketplace which makes it easy for consumers to purchase a product. The aim of this research is to determine the influence of electronic word of mouth and promotions on purchasing decisions on the Shopee marketplace in Batam. This research is of a quantitative descriptive type. And the sample used in this research was 400 respondents where this sampling was based on the population in Lubuk Baja District, Batam City. The sampling technique used is non-probability sampling, namely purposive sampling. The test techniques that will be used in this research are validity test, reliability test, multicollinearity test, heteroscedasticity test, R2 test, T test and F test. From this research the results show that electronic word of mouth has a positive effect on purchasing decisions, promotions have there is a positive influence on purchasing decisions. And simultaneously electronic word of mouth and promotions influence purchasing decisions, with a large influence of 53% while 47% is influenced by other variables. Keywords: Electronic word of mouth,Promotion, Purchasing Decisions.